Leo Strauss and Emmanuel Levinas : philosophy and the politics of revelation - Batnitzky, Leora, 1966- (Cambridge University Press, 2006)
Leo Strauss and Emmanuel Levinas, two twentieth-century Jewish philosophers and two extremely provocative thinkers whose reputations have grown considerably, are rarely studied together. This is due to the disparate interests of many of their intellectual heirs. Strauss has influenced political theorists and policy makers on the right while Levinas has been championed in the humanities by different cadres associated with postmodernist thought. In Leo Strauss and Emmanuel Levinas: Philosophy and the Politics of Revelation, first published in 2006, Leora Batnitzky brings together these two seemingly incongruous contemporaries, demonstrating that they often had the same philosophical sources and their projects had many formal parallels. While such a comparison is valuable in itself for better understanding each figure, it also raises profound questions in the debate on the definitions of 'religion', suggesting ways that religion makes claims on both philosophy and politics.